Investigations in liquid ammonia chemistry - Robert J. Reynolds (2000)
Reaction of PtCl2(PR3)2 with a solution of SOCl2 in NH3(1) is known to yield compounds of the type Pt(NSO)2(PR3)2. Reaction of PtCl2(PR3)2 with a solution of S02 in NH3(1) is known to yield compounds of the type Pt(S02(NH)2(PR3)2). The initial part of this work was to try and expand this field of synthetic chemistry, and investigate whether metal dichlorides would be amenable starting material for the production of metal bis-thionylimide compounds via a liquid ammonia route, as opposed to more traditional wet chemical methods. This was largely unsuccessful, with the exception of the production of Hg(NSO)2, which was verified by i.r. and Raman spectroscopy and mass spectroscopy. Reaction of PtCl2(PR3)2 with SeOCl2 in NH3(1) was also tried, in an attempt to produce a selenium analogue of the thionylimide compounds. This was not successful. Much Raman-spectroscopic work was undertaken to try and expand upon the data previously published by authors such as Chivers and Lelieur, with respect to the species present in solutions of S, SOCl2, SO2Cl2, S/Se and mixtures thereof in liquid ammonia. We were unfortunately unable to improve upon previously published work.